Crystal ball, virtual gallery C reation system for immersive environments - Almeida, R. N. de. (2021)
This paper presents a concept and a tool suite for authoring, configuring, organizing and displaying 3D virtual galleries, depicting multimedia content, like art, picture, movie or any other kind of media, which are appropriate for large-scale immersive virtual environments such as the CAVE™. A comparison was established by the authors with standard PC environments while experimenting virtual environments produced by Crystal Ball, showing the superior experience obtained by an installation of the type of CAVE™ that is in operation at Lousal, south of Portugal.